The shift from business to leisure: An industry perspective of motivators of business tourists’ transition to leisure tourists - Tan, Ai Ling *; Vijaya Malar, V. A. *; Chai, Anisha Mee Fong * (2021)
This study focuses on business events industry stakeholders’ perspectives on the issues surrounding the return of business event tourists as leisure tourists through the exploration of the push and pull factors from the supply side of business tourism industry. The business events industry is a vital service industry, and serves as a socioeconomic catalyst for any country as it not only generates significant revenue, but hosting a business event instils the host city with favourable conditions, which can become a pivotal driver for future development. Research showed that business tourists find potential leisure travel destinations when they go for their business trips and a focused effort by the tourism actors in a country can be a critical factor to enable the transition of such tourists. This implies that the right marketing strategies should be adopted to maximise the tourism outputs from every interaction. Existing literatures’ focus has been primarily on the motivations of the business and leisure travellers from the perspective of the traveller and not from any other industry stakeholders, thereby giving a limited understanding of underlying tourists’ motivation, attitude and behaviours. Hence, this study explored the factors that attract and the challenges that impact the business tourists’ revisit decisions in a leisure capacity as perceived by business events industry representatives. This study sought the perceptions of business events industry representatives as they provide services to business tourists and directly interact with them, thus are critical sources of information on business tourists’ behaviour. The industry representatives are more attuned to the motivations and expectations of the business tourists and it provides a functional perspective towards facilitating the transition of the business tourist into a leisure tourist. The push and pull theory is used as the theoretical underpinnings of this study as a means of determining the factors that attract and dispel business tourists to return as leisure tourists. This study used the inductive and explorative research design for its research objectives and industry representatives were selected using purposive sampling. Data was collected using semi-structured questions via face-to-face interviews. In addition, content analysis of the data was independently coded by two researchers as well as performing axial coding for coding purposes. The characteristics of business tourists and intention to visit as leisure tourists with relevant factors were categorised as themes. The findings of the research indicate several pull factors of what attracts travelers to Malaysia (people of Malaysia, nature and heritage, food and accommodation, shopping and nightlife). A key finding of this research that there is no effort at integrating the attractive elements of leisure travel in Malaysia within the business event agenda (i.e limited push factors). The existing gaps indicated by the respondents show a need for an integrated marketing mix strategy where the marketing mix should focus on leisure aspects for business tourists to enrich tour experiences and improve tourists’ satisfaction. It is evident that the different tourism segments function in silos rather than integrated under a holistic tourism value chain. There is a disconnect between the various tourism segments (leisure, business events) where each segment focuses only on its specific requirements rather than working together as different but inter-linked players in the total tourism value chain. Working as separate entities engaged in narrow orientations, is not a viable strategy as it limits the full extent to which the destination’s value can be realized. The underlying concerns evident through the research findings center on the perceived fragmentation of the tourism market and the lack of efforts by various stakeholders to promote Malaysia as a complete destination brand. Destinations should provide various offerings to cater to the diversity in the market and this means Malaysia should be presented as a comprehensive destination with various attractions that cater to both business tourists and leisure tourists. The paper therefore, suggests a collaborative approach needs to be adopted by relevant tourism stakeholders to ensure the success of Malaysian tourism in a highly competitive marketplace instead of working under market-specific fragmentations.